2022
DOI: 10.3389/fmicb.2022.999399
|View full text |Cite
|
Sign up to set email alerts
|

Response of bacterial community composition and co-occurrence network to straw and straw biochar incorporation

Abstract: Microbial decomposition plays a crucial role in the incorporation of straw and straw biochar (SSB) into soil. Lime concretion black soil (LCBS) is a typical low-medium crop yield soil, and it is also one of the main soil types for grain production in China. However, the link between SSB additions and soil bacterial communities in LCBS remains unclear. This study explored the effects of SSB incorporation on bacterial community composition, structure and co-occurrence network patterns at different soil depths an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…As identified by the network analysis, SD network is more complex and robustly stable than BC, as reflected by the high number of edge, average degree, graphic density, and average clustering coefficient (Figure 4). This result was partly consistent with the observation of Du, Zhang, et al (2022), who found that straw had positive effect on the bacterial network pattern. The interactions of soil microbial communities became strong in response to straw return, which demonstrates that the degradation of complex organic matter in SD soil may require a variety of microorganisms to work together (Yang, Bao, et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As identified by the network analysis, SD network is more complex and robustly stable than BC, as reflected by the high number of edge, average degree, graphic density, and average clustering coefficient (Figure 4). This result was partly consistent with the observation of Du, Zhang, et al (2022), who found that straw had positive effect on the bacterial network pattern. The interactions of soil microbial communities became strong in response to straw return, which demonstrates that the degradation of complex organic matter in SD soil may require a variety of microorganisms to work together (Yang, Bao, et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The RA of Sphingomonas in this study was affected by SRMs and associated with NFLs, which was significantly increased by BC at the N60 level but was significantly decreased by SD at the N0 level (Table S2). A previous study also suggested that the effect of straw return on the RA of Proteobacteria was related to the nitrogen level (Du, Zhang, et al, 2022). The sufficient air and organic nutrient conditions provided by BC might be responsible for the increase in Sphingomonas (Li, Song, et al, 2022; Li, Zheng, et al, 2022).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…During the fallow period (December), the soil bacterial Shannon index, Chao index, and Ace index were signi cantly higher under OM, MNPK, and ST treatments (OM > MNPK > ST). This may be a result of nutrients and soluble organic matter released from decomposed manure and straw that were not fully absorbed and utilized by roasted tobacco, with the accumulated nutrients stimulating microbial growth and increasing diversity (Ge et al 2021;Du et al 2022). In our study, no signi cant differences were observed in bacterial α-diversity..On the other hand,t ANOSIM analysis revealed that different sampling periods signi cantly affected bacterial β-diversity.…”
Section: Soil Bacterial Diversity and Functions In Response To Fertil...mentioning
confidence: 99%